THE USE OF GREEN ROOFS AS A SUSTAINABLE ALTERNATIVE TO URBAN CENTERS: A REVIEW. (REMUNOM, 2024)
The lack of knowledge and awareness about the benefits and implementation techniques of green roofs among construction professionals and building owners led the authors to conduct this study. These reasons include the lack of information and public policies that promote the use of green roofs, which can make their implementation difficult and limit their potential for environmental and economic benefits. Therefore, this study on green roofs is justified to promote knowledge, awareness and adoption of this sustainable practice, improves environmental impacts and provides economic benefits for building owners. The general objective of this article is to address the use of green roofs as a sustainable alternative in urban centers. The methodological proposal applied to materialize this study refers to the use of exploratory and descriptive bibliographic research, based on books, magazines and scientific articles to formulate references and information related to the topic. It should be noted that, for better development of the research, an analysis of other relevant studies was also carried out, given the breadth of the theme. This study will serve as a guide to the capacity of green innovation to transform urban environmental challenges into opportunities for sustainable development. With the increasing adoption of green roofs, we can envision a future in which our cities more deeply reflect the values ​​of sustainability, resilience and communion with nature.